Thin film nanopores (V, 10Ti)NxHy hydrogen storages - Guglya, A.G.; Marchenko, Yu.A.; Melnikova, E.S.; Vlasov, V.V.; Zubarev, E.N. (Вопросы атомной науки и техники, 2014)
This scientific paper delves into the findings of the investigation carried out to determine the adsorption and electrophysical characteristics of nanoporous (V, 10 at.% Ti)Nx films obtained using the ion beam-assisted deposition technique (IBAD). It has been shown that these films can accumulate more than 7 wt.% hydrogen at a relatively low pressure of 0,5 MPa. One part of it is accumulated in the grain boundaries and pores but another one forms the hydride phase. A complete release of hydrogen occurs at a temperature of 250 °C. During the hydrogen desorption the specific resistivity of (V, 10Ti)NxHy films is roughly increased by a factor of 10⁷.